2014
DOI: 10.1002/chir.22303
|View full text |Cite
|
Sign up to set email alerts
|

A Practical and Stereoselective Organocatalytic Alkylation of Aldehydes with Benzodithiolylium Tetrafluoroborate

Abstract: Recently, the direct substitution of allylic, benzylic, and tertiary alcohols has been achieved via SN 1-type reactions with catalytic amounts of Brønsted or Lewis acids. When a new stereogenic center is formed most of these transformations produce the desired product as a racemate, as these reactions proceed through carbenium ions. The arsenal of activation modes available in organocatalysis can be used to set up suitable reaction conditions in which chiral nucleophiles (enamine catalysis) or chiral electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The complete set of these reactions is beyond the scope of this review, but some notable examples have been mentioned for the interested reader. [99][100][101][102][103] MacMillan's group has also presented the photoredox mediated trifluoromethylation of arenes and heteroarenes including pyrroles, indoles, furans, thiophenes and notably, more complex substituted arenes such as Lipitor, the drug commonly used to treat high cholesterol. 104 The oxygenation of arenes has also been reported by Li and coworkers for a range of anisole derivatives.…”
Section: +mentioning
confidence: 99%
“…The complete set of these reactions is beyond the scope of this review, but some notable examples have been mentioned for the interested reader. [99][100][101][102][103] MacMillan's group has also presented the photoredox mediated trifluoromethylation of arenes and heteroarenes including pyrroles, indoles, furans, thiophenes and notably, more complex substituted arenes such as Lipitor, the drug commonly used to treat high cholesterol. 104 The oxygenation of arenes has also been reported by Li and coworkers for a range of anisole derivatives.…”
Section: +mentioning
confidence: 99%
“…We surprisingly found that benzodithiolylium tetrafluoborate 16 was commercially available, and its interesting chemistry was fully described 101. We have carefully optimized the alkylation of aldehydes with 16 , using a MacMillan secondary amine as the catalyst (Scheme ) 102. Notably, the reaction is performed in a mixture of water: CH 3 CN as the reaction solvent, where the carbenium ion is fully soluble.…”
Section: An Unexpected Journey: Carbenium Ions For Organocatalytic Snmentioning
confidence: 99%
“…No dried solvents or strong bases are necessary for the alkylation, and the procedure can be successfully used by undergraduate students 107. This organocatalytic alkylation was applied to the total synthesis of arundic acid,102 Lilial,108 and Bisabolans (Scheme ) 109…”
Section: An Unexpected Journey: Carbenium Ions For Organocatalytic Snmentioning
confidence: 99%